Increased Matrix Metalloproteinase-2 and Matrix Metalloproteinase-3 Concentrations in Corneal Epithelium of Patients with Recurrent Corneal Erosions - Katarzyna Jadczyk-Sorek; Wojciech Garczorz; Beata Bubała-Stachowicz; Tomasz Francuz; Ewa Mrukwa-Kominek (Journal of Ophthalmology)
Purpose. To assess the role of selected matrix metalloproteinases in defective corneal re-epithelization in patients with recurrent corneal erosions. Subjects. The study group (group 1) included patients with recurrent corneal erosions qualified for phototherapeutic keratectomy. The group 1 was divided into two subgroups regarding the etiology of recurrent corneal erosions: group 1A, Cogan’s basement membrane dystrophy, and group 1B, trauma. The control group (group 2) included patients with healthy eyes qualified for Epi-Bowman Keratectomy. Methods. The analyzed material was the corneal epithelium collected during phototherapeutic keratectomy or Epi-Bowman Keratectomy in the study or control group, respectively. Matrix metalloproteinases concentration was determined by an immunohistochemical method using Human Magnetic Luminex® Assay. Results. The study revealed a statistically significantly higher concentration of matrix metalloproteinase-2 in group 1 compared to the control and a statistically significantly higher concentration of matrix metalloproteinase-3 in group 1 compared to the control. Conclusions. The results obtained in the study can prove that matrix metalloproteinase-2 and matrix metalloproteinase-3 having the ability to dissolve anchoring fibers and the corneal epithelial basement membrane could be responsible for epithelial instability and their accumulation in the corneal epithelium may induce recurrence of erosion.